A systematic review of cognitive effects of exercise in depression. (22nd January 2017) - Brondino, N.; Rocchetti, M.; Fusar‐Poli, L.; Codrons, E.; Correale, L.; Vandoni, M.; Barbui, C.; Politi, P.
Abstract : Objective: The aim of the present systematic review and meta‐analysis was to evaluate the impact of physical exercise on cognitive symptoms in depressed adult patients. Methods: Systematic literature search was performed in Web of Science™ and CINAHL from inception to August 2016. Two reviewers independently selected randomized trials evaluating the effect of exercise on cognitive functions in patients with a validated diagnosis of depression. Outcome measures included global cognition and different cognitive domains (speed of processing, attention/vigilance, working memory, verbal and visual memory, and reasoning). Results: Eight trials met inclusion criteria (637 patients). A fixed‐effects model showed absence of beneficial effect on global cognition (Hedges' g = 0.07, 95% CI −0.08 to 0.24, I 2 = 0%) as well as on specific cognitive domains. Sensitivity analyses did not show an impact of exercise in studies with shorter intervention duration compared to longer trials (between group heterogeneity Q = 3.564, d f = 1, P = 0.059), single session per week compared to multiple sessions ( Q = 2.691, d f = 1, P = 0.101) and low exercise intensity compared with moderate/high intensity ( Q = 2.952, d f = 1, P = 0.086). Conclusion: Our meta‐analysis did not observe a substantial benefit of physical exercise on cognitive symptoms in depression.